Local Working of Patents: a Comparative Study of Europe and Indonesia - Іка Деві; Харіц Нуман; Нені Рухаені; Діні Хеніарті (Проблеми Законності, 2023)
This study analyzes the implementation mechanism of local working patents from both European and Indonesian perspectives, using normative research methods and secondary data obtained from library research. The implementation of Patent Act Number 13 of 2016 has faced criticism from various parties, including patent holders who find it complicated and difficult to comply with the local working patent provisions. The Ministry of Law and Human Rights has issued regulations to facilitate patent holders who are unable to implement Article 20 by allowing them to request patent postponement. However, the Job Creation Act No. 11 of 2022 has made it easier for patent holders to fulfill their obligations regarding local working patents. The Directorate General of Intellectual Property (DGIP) is responsible for monitoring, evaluating, and reporting on intellectual property protection. However, rules and procedures related to monitoring mechanisms, especially those related to implementing local working patents, have not been fully regulated by the DGIP Office.